Sonar gas flux estimation by bubble insonification: application to methane bubble flux from seep areas in the outer Laptev Sea; The Cryosphere; Vol. 11, iss. 3 - Leifer I. S. Ira; Chernykh D. V. Denis; Shakhova N. E. Nataljya Evgenjevna; Semiletov I. P. Igor Petrovich (2017, 2017)
Title screen